2008
DOI: 10.1007/s00210-008-0363-y
|View full text |Cite
|
Sign up to set email alerts
|

A role for atorvastatin and insulin combination in protecting from liver injury in a model of type 2 diabetes with hyperlipidemia

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a major complication linked with the metabolic syndrome associated with dyslipidemia, inflammation, and oxidative stress. Impact of type 2 diabetes with hyperlipidemia in NAFLD has to be established, as well as the utility of commonly prescribed anti-diabetic and lipid-lowering agents in improving liver injury markers. Genetic type 2 diabetic Goto-Kakizaki rats were fed with a high-fat diet to test hepatic effects of type 2 diabetes with hyperlipidemia and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…Therefore, these models are unable to facilitate systematic examination of the effect of timed onset of diabetes added to a high-fat diet or to a metabolic syndrome phenotype; however, interventions targeting hyperglycemia in diabetes, for example, can be trialled in them. To date, these interventions are relatively few and include hepatic antisteatotic and systemic antiinflammatory effects of a selective dipeptidyl peptidase-IV (DPP-IV) inhibitor in a murine diabetes model (126), statin therapy with either metformin (127) or insulin (128) in db/db fat-fed mice, and peroxisome proliferator-activated receptor (PPAR)-␣ agonist treatment in the foz/foz cholesterol-fed model (129). This limited series of studies is collated in Table 2 and collectively implicates dyslipidemia, insulin resistance, and possibly hyperglycemia in effects of type 2 diabetes on NAFLD and its progression.…”
Section: Pathogenic Mechanisms In the Relationship Of Nafld Andmentioning
confidence: 99%
“…Therefore, these models are unable to facilitate systematic examination of the effect of timed onset of diabetes added to a high-fat diet or to a metabolic syndrome phenotype; however, interventions targeting hyperglycemia in diabetes, for example, can be trialled in them. To date, these interventions are relatively few and include hepatic antisteatotic and systemic antiinflammatory effects of a selective dipeptidyl peptidase-IV (DPP-IV) inhibitor in a murine diabetes model (126), statin therapy with either metformin (127) or insulin (128) in db/db fat-fed mice, and peroxisome proliferator-activated receptor (PPAR)-␣ agonist treatment in the foz/foz cholesterol-fed model (129). This limited series of studies is collated in Table 2 and collectively implicates dyslipidemia, insulin resistance, and possibly hyperglycemia in effects of type 2 diabetes on NAFLD and its progression.…”
Section: Pathogenic Mechanisms In the Relationship Of Nafld Andmentioning
confidence: 99%
“…For carbonyl determinations, extracts were prepared as stated before (Matafome et al, 2009(Matafome et al, , 2011.Samples were derivatized with 10 mM 2, 4-dinitrophenylhydrazine (DNPH) in 10% trifluoroacetic acid (TFA) and the reaction was stopped with trichloroacetic acid (TCA). After centrifugation (14000×g, 5 minutes, 4°C) pellets were washed twice in ethyl acetate: ethanol 1:1 (v/v).…”
Section: Western and Dot Blottingmentioning
confidence: 99%
“…We have previously demonstrated hepatic inflammatory infiltration in models of hyperglycaemia and hyperlipidemia (Matafome et al, 2009(Matafome et al, , 2011. Several studies demonstrated that similar events occur in adipose tissue in models of diet-induced obesity and in obese individuals (Cancello et al, 2005;Lumeng et al, 2007;Olefsky & Glass, 2010;Pang et al, 2008).…”
mentioning
confidence: 94%
“…Diabetes mellitus causes dysregulation in carbohydrate, fat and protein metabolism, which may lead to serious complication, including blindness, renal failure, liver injury, nerve damage, and atherosclerosis [3, 4]. Diabetes-induced liver injury has received much attention, which has been illustrated from inflammatory responses, liver fibrosis and lipid accumulation [5, 6]. Among these responses, liver inflammation is a critical mechanism, and several studies have reported that anti-inflammation agents showed efficacy in reducing blood glucose level, enhanced insulin activity and protected diabetes caused by liver injury, and it may be a potential therapeutic target for this disease [7].…”
Section: Introductionmentioning
confidence: 99%